2 - Negotiated Economic Opportunity and Power: Perspectives and Perceptions of Street Vending in Urban Malawi: DOI: 10.4314/ad.v30i4.22239 - Jimu, Ignasio Malizani (Africa Development, 2005)
It is least acknowledged in daily discourses that street vending is a very impor tant phenomenon. Little wonder that street vending involves negotiating for space in all its manifestations: physical space, economic opportunity and power. The vendors are coerced by both local urban and national authorities and sometimes the public at large to justify or negotiate acceptance. Very often such intentions are blind to the most basic and yet fundamental aspect that street vending is a pragmatic grassroots response to bleak socio-economic and changing political realities that have not of late spared anyone. Street vending appears in all fair ness a means to legitimate ends. Hence, access to vending spaces should be perceived as a human rights issue. Otherwise, intentions to the contrary over look the needs and capacity of street vendors to communicate, reorient and police each other in various and meaningful ways. Any discussion of the place of street vending in the urban economy of Malawi should therefore consider why and how individual street vendors become what they are - vendors. These perspectives can enrich our defective understanding and parochial pursuits of idealized versions of regulation that are hardly appropriate for a pressurized and underdeveloped country and also for a negotiated idea of the social consumption of space that we should alway aim at.